Rhetorical trainings: a symbiosis of communications theory and practice - Aleksandrova, Donka (Media and Language, 2020)
The Department of Rhetoric, which has been preparing professional communicators for various areas of public life (journalists, politicians, teachers, businessmen, activists from the non-governmental sector, etc.) for more than four decades, periodically organizes scientific and theoretical conferences on various topics of the history, theory and practice of persuasive communication. This year (September 27, 2019) the format was changed - for the first time the organizers set themselves the goal of holding a Seminar, uniting the efforts of established and young communication specialists in order to discuss the trainings, their theoretical and, above all, applied aspects, without which effective communication is impossible. The composition of the participants in the Seminar once again unequivocally emphasized the interdisciplinary nature of rhetoric - in addition to lecturers, doctoral students and master’s students from the Department of Rhetoric, philosophers, sociologists, political scientists, journalists, lawyers, philologists, etc. participated in the discussion. The organizer of this theoretical and applied forum was a team of young lecturers and doctoral students under the leadership of Assoc. Prof. Dr. Neli Stefanova, specialist in political and intercultural communication, director of the Master’s Program "Rhetoric".